A High‐Performance Self‐Powered Photodetector Based on MAPbBr3 Single Crystal Thin Film/MoS2 Vertical Van Der Waals Heterostructure (Adv. Mater. Interfaces 27/2022). Issue 27 (23rd September 2022) - Xu, Zhongquan; Zeng, Yonghong; Meng, Fanxu; Gao, Shan; Fan, Sidi; Liu, Yi; Zhang, Yule; Wageh, Swelm; Al‐Ghamdi, Ahmed A.; Xiao, Jing; Guo, Zhinan; Zhang, Han
Abstract : Single Crystal MAPbBr3 /MoS2 Vertical vdW Device A strategy on combining single crystal perovskite with 2D materials into a vertical van der Waals (vdW) for high‐performance self‐powered photodetector fabrication is proposed by Zhongquan Xu, Jing Xiao, Zhinan Guo, and co‐workers in article number 2200912 . The single crystal MAPbBr3 /MoS2 vertical vdW device shows excellent photovoltaic and photoelectric properties, which are attributed to the built‐in electric field at the interface between two materials and the short channel distance between two electrodes.